Evaluation of Self‐Esteem and Depression Symptoms in Depressed and Nondepressed Subjects Treated with OnabotulinumtoxinA for Glabellar Lines. Issue 7 (6th March 2013) - Hexsel, Doris; Brum, Cristiano; Siega, Carolina; Schilling‐Souza, Juliana; Forno, Taciana Dal'; Heckmann, Marc; Rodrigues, Ticiana C.
<x xml:space="preserve">Abstract</x> Background Botulinum toxin type A (BoNT‐A) injection has become the most popular cosmetic nonsurgical procedure, and it has been suggested that BoNT‐A injections may improve emotional states when frown lines are treated. Objectives To evaluate symptoms of depression and self‐esteem before and after onabotulinumtoxinA (ONA) injections in the glabella in subjects with and without depression. Methods Twenty‐five subjects with depression were allocated into one group and 25 subjects without depression were matched to those according to demographic characteristics. The Beck Depression Inventory (BDI) and Rosenberg Self‐Esteem Scale (RSES) were used to assess depression symptoms and self‐esteem, respectively. Patients were assessed up to 12 weeks after the intervention. Results Patients with depression had significant improvement in depression symptoms after ONA injections. The maximum effect occurred within the first 8 weeks after treatment. A significant reduction from baseline in BDI score and significant improvement in self‐esteem were also observed in patients with depression. Conclusion This research presents new data regarding BoNT‐A as a potential treatment to improve depression symptoms in patients with Major Depressive Disorder. Self‐esteem scores alone cannot explain the improvement in depression symptoms.